BIVALVE MOLLUSC FARMING AS A GLOBAL MODEL FOR PRODUCTION AND VALORIZATION OF SUSTAINABLE FOOD RESOURCES AND LONG-TERM CARBON BIOSTORAGE - SUMMA, Daniela (Università degli studi di Ferrara, 2025)
Sustainable development is a type of economic growth in harmony with nature, which includes the concepts of justice, opportunity and equality. Shellfish farming, in Italy and in the world, is a deep-rooted practice that combines tradition and innovation. This activity can make a significant contribution to the achievement of the Sustainable Development Goals (SDGs) established by the 2030 Agenda in terms of food security, management and conservation of marine ecosystems and socioeconomic development, especially of coastal communities. In this scenario, the project of this thesis aims to analyze Italian shellfish farming under multiple aspects: nutritional, identifying the anti-inflammatory properties and the presence of bioactive compounds, environmental, through LCA analysis, and economic, through the analysis of the profit and loss account. There are many species of economic and cultural relevance in the fishing sector; However, three species of bivalves can be identified that play an important role not only in the Italian aquaculture sector, but also in the global one: the Manila clam Ruditapes philippinarum, the mussel Mytilus galloprovincialis and the oyster Crassostrea gigas. The Manila clam was introduced in the 1980s and quickly conquered the Italian market, establishing itself especially in lagoon environments such as that of Goro (FE) which has become a leader in the production of this bivalve. An investigation of the historical environmental sustainability of the entire fishing and aquaculture sector of Goro has highlighted how the arrival of the Philippine clam, in addition to increasing the economic well-being of the community, has led to the reduction of more impactful fishing systems (trawling and gillnets) and to the relocation of production activity from the open sea to within the lagoon area. This leads to lower fuel consumption and the consequent reduction of the associated environmental impact. As regards mussel farming, the analysis in the United Kingdom has offered the opportunity to ...